PELATIHAN PENERAPAN SENSOR SUARA UNTUK RUANGAN CERDAS DALAM MENDETEKSI ASAP DAN PINTU OTOMATIS PADA PT. TNC - Teddy Surya Gunawan; Wulan Dari; Muhammad Sadikin (Jurnal Pengabdian Masyarakat Berbasis Teknologi, 2021)
The use of various devices that can work automatically so that they can help alleviate human activities which will certainly use a lot of power if their use is not controlled properly and optimally according to needs such as those used in the study room, namely lighting and air conditioning (fans, air conditioners). lights, etc.). So with the existence of a system of controlling electricity usage in the study room that can work independently, it is hoped that it can save more power usage. Automation of power consumption in microcontroller-based learning rooms is a tool used to detect and display human capacity and temperature in the study room and to regulate the active or inactivity of air conditioners equipped with smoke sensors and sound sensors. The air conditioner will turn on when there are people in the room and the room temperature exceeds the set point (set value) temperature that has been set as desired.  This tool consists of a microcontroller as the main controller, a photodiode to detect people entering and leaving the room, LM35 as a temperature detector in the room, LCD (Liquid Crystal Display) as a display of the number of people and the temperature in the room